Resurgence of a forgotten Southern Brazil endemic species: taxonomic position, redescription, and spatio-temporal distribution of Porosagrotis carolia Schaus, 1929 (Lepidoptera: Noctuidae: Noctuinae) - Dias, Fernando M. S.; Specht, Alexandre; Blas, German San; Casagrande, Mirna M.; Mielke, Olaf H. H. (Zootaxa, 2017)
The taxonomy of the hitherto unplaced taxon Porosagrotis carolia Schaus, 1929 is evaluated and the name is taken out of taxonomic limbo and combined with Feltia Walker, 1856. Feltia carolia comb. nov., described from a single female specimen, is redescribed, including the first description of the male. Head, thorax and its appendages, and male and female genitalia are illustrated through photographs and line drawings; photographs of the holotype and a distribution map for the species is provided. Additionally, the spatio-temporal occurrence of the species in Rio Grande do Sul was assessed by monthly standardized samplings with light traps from January of 1998 to December of 1999 in ten different physiographical zones of the state. Our results suggest that F. carolia comb. nov. is univoltine and goes through prepupal and pupal estival diapauses. The assessment of the distribution of the species, based on the standardized samplings and specimens deposited in entomological collections, suggests that F. carolia comb. nov. is restricted to the southern Brazilian Campos, a mostly neglected environment discontinuously distributed in mountainous plateaus of the southern Mata Atlântica biome.